2022
DOI: 10.15421/012205
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiles, antioxidant and antimicrobial activity of Actinidia polygama and A. arguta fruits and leaves

Abstract: Plants of two species of Actinidia genus grown in an adverse steppe climate were examined in terms of secondary metabolites’ accumulation, antioxidant potential, and antimicrobial ability. The aim of the work was to reveal whether the introduced plants A. arguta and A. polygama retain their well-known health benefits. Total content of polyphenols (549.2 and 428.1 mg GAE/100 g FW, respectively), flavonoids, and phenolic acids as well as total antioxidant activity and reducing power of the fruit isopropanol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…The primary raw material from Acnitidia shrubs is its fruits, which are rich in polyphenols and vitamin C [24]. However, it should be noted that in most cases, secondary metabolites with biological activity in plants are stored in all parts.…”
Section: Resultsmentioning
confidence: 99%
“…The primary raw material from Acnitidia shrubs is its fruits, which are rich in polyphenols and vitamin C [24]. However, it should be noted that in most cases, secondary metabolites with biological activity in plants are stored in all parts.…”
Section: Resultsmentioning
confidence: 99%
“…The crude extracts of A. arguta fruit and leaves notably inhibited clinical strains of Pseudomonas aeruginosa and Escherichia coli, which were resistant to the action of ofloxacin. The inhibitory effects of the plant extracts on clinical strains of Klebsiella pneumoniae and Acinetobacter baumannii were comparable with the effect of ofloxacin [70]. In addition, Macedo et al (2023) studied an extract of A. arguta, which displayed antimicrobial activities against Staphylococcus aureus (MIC = 32 mg/mL) and Pseudomonas gingivalis (MIC = 64 mg/mL) and reduced the growth rate of Escherichia coli [71].…”
Section: Other Pharmacological Effectsmentioning
confidence: 91%
“…Khromykh et al (2022) studied the antioxidant activities of components such as polyphenols in the peels and pulps of A. arguta. The results indicated that the peels had stronger reducing power and total antioxidant capacity compared with the pulps [70]. The best processing extract of A. arguta exhibited exceptional antioxidant and antiradical activities, including ABTS, ferric-reducing antioxidant power (FRAP), superoxide anion radical, hypochlorous acid, and peroxyl radical scavenging [71].…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…За дії полютантів різного походження на живі організми проявляються неспецифічні реакції, однією з яких є посилення вільно-радикальних процесів та підвищення активності антиоксидантних ферментів, зокрема супероксиддисмутази (Lykholat & Chernaya, 1999;Ahmad et al, 2010;Boran & Ugur, 2017;Hasanuzzaman at al., 2017;Lykholat et al, 2019;Li et al, 2020;Jadczak Sanna et al, 2020;Khromykh et al, 2022;Sanna et al, 2022).…”
Section: вступunclassified